M-Center in Neutron-Irradiated 4H-SiC - Ivana Capan; Tomislav Brodar; Takahiro Makino; Vladimir Radulovic; Luka Snoj (Crystals, 2021)
We report on the metastable defects introduced in the n-type 4H-SiC material by epithermal and fast neutron irradiation. The epithermal and fast neutron irradiation defects in 4H-SiC are much less explored compared to electron or proton irradiation-induced defects. In addition to the carbon vacancy (Vc), silicon vacancy (Vsi) and carbon antisite-carbon vacancy (CAV) complex, the neutron irradiation has introduced four deep-level defects, all arising from the metastable defect, the M-center. The metastable deep-level defects were investigated by deep level transient spectroscopy (DLTS), high-resolution Laplace DLTS (L-DLTS) and isothermal DLTS. The existence of the fourth deep-level defect, M4, recently observed in ion-implanted 4H-SiC, has been additionally confirmed in neutron-irradiated samples. The isothermal DLTS technique has been proven as a useful tool for studying the metastable defects.